IDENTIFICATION OF THE KINDS AND COMPOSITIONS OF RADIOISOTOPE AND OTHER ELEMENTS WITHIN THE MINERAL SAMPLES WITH USING MULTICHANNEL ANALYZER (DIGITAL SPECTRUM ANALYSIS) AND NEUTRON ACTIVATION ANALYSIS AT SUBDISTRICT OF AMARASI, KUPANG WEST TIMOR ISLAND - Bartholomeus Pasangka; Suari Suari; Irvandi Gorby Pasangka (Jurnal Fisika : Fisika Sains dan Aplikasinya, 2021)
The problems analyzed in this research are the kinds and compositions of radioisotope and other elements within the mineral samples in the West Timor Island. The purposes of the research: 1) to investigate and determine the kinds of radioisotope in the mineral sample, 2) to determine radiation energy, counts, half-life, and percentage of radioisotope content in the mineral sample, 3) to investigate other elements in mineral sample. The methods of the research include observation, survey, sampling, spectrometry, analysis, and interpretation. On the observation, survey, and sampling steps, the 50 samples taken are distributed at the survey location. Those samples are analyzed with the several steps including: drying samples, refining, burning until temperature 800o C, stabilization and drying again. All samples are analyzed with spectrometry system on the multichannel analyzer (MCA) which can separate element of the samples. The other elements (only non- radioactive samples) are analyzed by neutron activation analysis with steps comprise of: 1) the dust and standard samples are balanced 0.50 grams up to 1.00 grams and put into the poliethilene capsule and irradiated during three hours in research reactor (Hoger Onderwijs Reactor with MTR-fuel assemblies and low enriched U-235: <20%) with the same time. After irradiation finished, the field and standard samples are refrigerated during one week, so the all samples with short half life decay finished. Furthermore, the samples are analyzed by gamma spectrometry for determining the other elements in mineral samples.The results obtained are the kinds of radioisotope content within the mineral samples consist of Actinium series 50%, Uranium 25%, and Thorium 25% component and other association elements, also energy radiation, counts, half life, and percentage of radioisotope content within the mini sample respectively revolved between 26.6 keV up to 1562.3 keV,1 cps up to 24867cps, 3.16 minutes up to 1.405 x 1010 years, and 0.19% up to 99.00%. The main elements on Actinium series within the samples of mine comprise of U-235, Th-231, Pa-231, Th-227, Bi-211, and Rn-219, and other isotopes Bi-212, Th-232, Pb-212, Pa-234, Ac-228, Ra-226, and Pb-214, with energy radiation, counts, half life, and percentage of radioisotope element deposit respectively revolved between 26.6 keV up to 426.9 keV, 1 cps up to 24867 cps, 7.038 x 108 years up to 1.405 x 1010 years, and 1.0% up to 18.7 %.The association elements consist of Am-241, Cs-134, Cs-136, Cs-138, Ce-141, Ce-144, Ba-133, Ba-140, Cd-109, Se-75, Te-132, Co-57, Mo-99, Kr-85, Kr-88, Kr-89, Sb-122, Sb-124, Sb-125, Xe-125, Xe-135, Xe-138, I-124, I-125, I-130, I-131, I-132, I-134, I135, Br-82, Y-92, Y-93, Y-94, W-187, Sr-91, Sr-92, Sr-93, Rb-89, Rh-105, Sn-133, Nb-94, Nb-96, Nb-97, Cr-51, Eu-152, and Tc-96. The other elements are detected by neutron activation analysis consist of: Fe-59, Xe-133m, Xe-135m, Y-91m, Zr-97, Ni-65, Be-7, Ag-110m, As-76, Cr-52, Au-198, and Ca-21.